1990
DOI: 10.1902/jop.1990.61.3.197
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Palatal Grooves in Upper Incisors and Periodontal Complications

Abstract: Palatal groove is a rare morphological defect of upper incisors, frequently associated with localized destruction of periodontal tissue with endodontic complications. In this study, a sample of 1,081 male, young adult subjects, aged 20 to 22, palatal grooving was recorded in 11 (1.01%) subjects, affecting 15 incisors. Among 634 adult subjects, aged 35 to 50, with periodontal disease, palatal groove was found in 5 (0.79%) incisors. Second incisors were more frequently (75%) associated with this anomaly. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 4 publications
0
21
1
Order By: Relevance
“…PGG can be classified by its location as distal, mesial, or central patterns as summarized in Table 1 16. Storrer et al reported that 9.58% of maxillary lateral incisors showed PGG in an investigation of 73 extracted teeth, with the groove always located in the center of the lingual area 12.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…PGG can be classified by its location as distal, mesial, or central patterns as summarized in Table 1 16. Storrer et al reported that 9.58% of maxillary lateral incisors showed PGG in an investigation of 73 extracted teeth, with the groove always located in the center of the lingual area 12.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prognosis for a tooth with PGG depends on several factors: the location of the groove, severity of the accompanying periodontal disease, accessibility to the defect area, and type of groove (shallow/deep or long/short) 1662. If the groove is shallow and terminates before the CEJ (confined to the crown of the tooth), the prognosis is good.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[6,[21][22][23] A study by Bacić et al [4] indicated that 1.01% of extracted maxillary incisors investigated presented with a PGG, whereas Kogon [21] and Pécora et al [24] reported a prevalence of 4.6% and 3.9%, respectively. PGGs are usually found in the maxillary lateral incisors and occur less frequently in the central incisors.…”
Section: Discussionmentioning
confidence: 99%
“…This malformation is known by different names, including the radicular groove, [3] a palatal groove, [4] a radicular lingual groove, [5] a disto-lingual groove, [6] a vertical developmental radicular groove, [5] a cinguloradicular groove, [7] a developmental radicular anomaly, [8] an interruption groove, [9] and a coronoradicular groove. [10] Although the exact etiology of PGGs remains unclear, alteration of genetic mechanisms, enfolding of the enamel organ and Hertwig's epithelial root sheath, and the effort required to form another root are considered as causal elements of PGG.…”
mentioning
confidence: 99%
“…However, grooves on the mesial and distal surfaces are more frequently associated with periodontal pockets. [910] Distal and mesial location of the groove can be considered a clinically adverse factor, since plaque more rapidly accumulates in these regions and are removed with greater difficulty. [10] In the present case, the groove was located on the distopalatal aspect of maxillary lateral incisor.…”
Section: Discussionmentioning
confidence: 99%